Evaluasi Ketersediaan Shelter Rumah Aman Dalam Mewujudkan Kota Layak Anak Di Kota Surabaya - Devy Pramudiana, Ika; Octafiani, Putri; Roekminiati, Sri (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The city of Surabaya has been selected as a Child-Friendly City since 2014. However, cases of violence against children in the city of Surabaya are still relatively high compared to neighboring cities. The purpose of this study is to describe and analyze data which includes: 1) The performance of the Child-Friendly City policy in preventing and overcoming cases of child violence; and 2) What factors support and hinder the implementation of the Child-Friendly City policy. This research was conducted using evaluation elements from William N. Dunn, namely effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. This study uses the analysis method according to Miles & Huberman, namely data reduction, data presentation, and drawing conclusions or verification. This research uses a qualitative approach, data collection techniques based on interviews, documentation, and observations. The results of this study show that the evaluation of the Child-Friendly City policy has gone quite well, which can be seen from 6 elements. The first is effectiveness, the Child-Friendly City policy program has been effective with the support of a safe house shelter construction program as a place for children who are facing the law. The second is efficiency, the strategy that has been carried out by the DP5A is to make regional regulations to support the program and also the safe house shelter program is free of charge. The third is adequacy, judging from the many programs that support this Child-Friendly City policy, such as PUSPAGA, Safe House Shelter, and others. Fourth, namely leveling, for socialization there are several supporting programs that not many people know about, such as safe house shelters because this program is secret. Then for socialization from DP5A, it continues to contribute to the agencies in the city of Surabaya. The fifth is responsiveness, which can be seen from the crowded children's homes and the increasing number of child-friendly schools. Sixth, the stipulation that the Child-Friendly City policy can reduce the number of violence in the city of Surabaya. However, there are inhibiting factors such as the lack of socialization to the public about what are the supporting programs of this policy and there are still some mischievous individuals in their duties, thus causing several small problems. The author's suggestion for the city of Surabaya is to continue to socialize the community so that the public knows about this policy and also so that the younger generation can also contribute to the implementation of this program.